2019
DOI: 10.3390/ani9070467
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Xylanase and Arabinofuranosidase Combination on the Growth Performance, Lipid Peroxidation, Blood Constituents, and Immune Response of Broilers Fed Low-Energy Diets

Abstract: The present study was conducted to examine that impact of dietary xylanase (Xyl) and arabinofuranosidase (Abf) supplementation on the performance, protein and fat digestibility, the lipid peroxidation, the plasma biochemical traits, and the immune response of broilers. A total of 480, un-sexed, and one-day-old broilers (Ross 308) were randomly divided into three treatments with eight replicates, where chicks in the first treatment were fed basal diets and served as the control, chicks in the second treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 40 publications
12
34
0
Order By: Relevance
“…Less amount of feed is required to produce meat and eggs, and fewer excess nutrients are excreted, thus reducing nutrients available for pathogen proliferation in the hind gut and in the litter ( 16 ). The utilization of low-energy diets to demonstrate the potential of xylanase has been adopted by multiple researchers ( 17 , 18 ). Saleh et al ( 18 ) showed that supplementation of xylanase and arabinofuranosidase to diets formulated with 90 kcal/kg less apparent metabolizable energy (AME) than a standard diet improved growth performance, nutrient digestibility, and immune response of broilers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Less amount of feed is required to produce meat and eggs, and fewer excess nutrients are excreted, thus reducing nutrients available for pathogen proliferation in the hind gut and in the litter ( 16 ). The utilization of low-energy diets to demonstrate the potential of xylanase has been adopted by multiple researchers ( 17 , 18 ). Saleh et al ( 18 ) showed that supplementation of xylanase and arabinofuranosidase to diets formulated with 90 kcal/kg less apparent metabolizable energy (AME) than a standard diet improved growth performance, nutrient digestibility, and immune response of broilers.…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of low-energy diets to demonstrate the potential of xylanase has been adopted by multiple researchers ( 17 , 18 ). Saleh et al ( 18 ) showed that supplementation of xylanase and arabinofuranosidase to diets formulated with 90 kcal/kg less apparent metabolizable energy (AME) than a standard diet improved growth performance, nutrient digestibility, and immune response of broilers. The ability of xylanase to improve utilization of energy as a result of fiber hydrolysis and release of trapped nutrients could potentially allow for feeding diets with lower energy content thus reducing cost of production.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been reported that activities of digestive enzymes (lipase, amylase, and trypsin) increase with age (Noy and Sklan 1979;Nitsan et al 1991;Jin et al 1998). Therefore, supplemental exogenous enzymes could optimize the digestibility of CP and consequently growth performance (body weight gain and feed conversion ratio) of broiler chickens (Jiang et al 2008;Angel et al 2011;Kalmendal and Tauson 2012;Yegani and Korver 2013;Saleh et al 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…In according with these results, Kehlet and Sims (2015) demonstrated that diets with 2% lower energy and supplemented with Bacillus Subtilis have final live weights equal to those of nonsupplemented diets with 2% higher energy. Also, Saleh et al (2019) indicated that feeding low-energy diet significantly decreased body weight compared to that of the control group, whereas diet supplemented with enzymes increased body weight which may be due to the function of enzymes mixture that had a positive effect on the energy utilization (Cowieson and Ravindran, 2008). Different results were reported by Flores et al (2016) who found that the inclusion of xylanase did not have significant impact on body weight or body weight gain throughout the experiment compared to the control group.…”
Section: Carcass Yieldmentioning
confidence: 89%